Nightfire. - Abramovic, Marina & Ulay; Bos, Saskia; Dumas, Marlene; Fortuyn/O'Brien; Kemps, Niek; Leonardo; Mol, Pieter Laurens; Puckey, Tom; Rilke, Rainer Maria; van Duyn, Edna; van der Heyden, J., C.J. (Amsterdam : De Appel Foundation Amsterdam, 1988)
Fortuyn/O'Brien ; Kosuth, Joseph ; Nagasawa, Hidetoshi ; Dumas, Marlene ; Byars, James Lee ; Bagnoli, Marco ; General Idea ; Adams, Dennis ; Acconci, Vito ; Abramovic, Marina & Ulay ; Lavier, Bertrand ; Muñoz, Juan ; Pitz, Hermann ; Odenbach, Marcel ; Casebere, James ; Kounellis, Jannis ; Anselmo, Giovanni ; Gerdes, Ludger ; Daniels, René ; Puckey, Tom ; Bazile, Bernard ; Séchas, Alain ; Bloom, Barbara ; Baldessari, John ; Lawler, Louise ; Boltanski, Christian ; Palestine, Charlemagne ; Urban, Nikolaus ; De Vier Evangelisten ; Iglesias, Cristina ; Kemps, Niek ; van der Heyden, J.C.J. ; van Elk, Ger ; Nordman, Maria ; Jonas, Joan ; Spalletti, Ettore ; Horn, Rebecca ; Schütte, Thomas ; Bastiaans, Christiaan ; Zaugg, Rémy ; Fritsch, Katharina ; Partenheimer, Jürgen ; Ruthenbeck, Reiner ; Gudmundsson, Sigurdur ; Bustamante, Jean-Marc ; Merz, Gerhard ; Lum, Ken ; Weiner, Lawrence ; Fischli & Weiss ; Graham, Dan ; Wall, Jeff ; Copers, Leo ; Rosenbach, Ulrike ; Mol, Pieter Laurens ; Dujourie, Lili ; Fabro, Luciano ; Holzer, Jenny
Nightfire, De Appel, Amsterdam, 20.12.'87 - 31.1.'88, This publication is issued as bulletin 88/1, May 1988
Engels
boek